Wordsworth's Crisis of Imagination - Domines Veliki, Martina (2011)
The article departs from an assumption that in writing The Recluse Wordsworth wanted to present a single man’s life within the conventions of the classical epic thus elevating the genre of autobiography to the highest aesthetic status. His autobiographical endeavour is the result of secularization of the seventeenth- and eighteenth- century religious autobiographies grounded in the narrative of confession and conversion based on the literary model of St. Augustine’s Confessions. In writing about his life Wordsworth aspires to truth as the highest standard and he wants to traverse the trajectory of his life in order to discover the amplitude of his mind, the importance of his vocation as a poet. Thus, his autobiography is above all an act of self-interpretation in which he becomes entangled in the logocentric worldview believing in the ability of written language to recuperate the emotions found in the speech of ordinary men and the innocence of childhood experiences. The poet has two tools to help him out on his way to the past: memory and imagination. Where memory leaves lacunae in the poet’s sense of the self, imagination is there to draw on an infinitely repeatable ‘I am’. Imagination accounts for the affirmative self and the positive sublime arising from the poet’s feeling of unity with nature. However, the forms of nature are capable of negating the mind, emptying it of all self-awareness, thus creating a poet of solitary, apocalyptic scenes. These two romantic selves, the affirmative and the negative one, meet in Wordsworth and they account for the tension in his poetry.
Projekt MZOS
ENG